Effect of Data Assimilation on Basin Evapotranspiration Simulation - YIN Jian; QIU Yuanhong; ZHANG Bin (Renmin Zhujiang)
In order to study the correction of hydrological process, especially evapotranspiration simulation by data assimilation, this paper constructs a deterministic ensemble Kalman filter assimilation system based on time variant gain model (TVGM) and remote-sensing evapotranspiration model, analyzes the simulation accuracy by the observation of watershed discharge and sub-basin evapotranspiration, and further studies the simulation accuracy, change process and assimilation calibration effect in terms of the spatial and temporal distribution of evapotranspiration. The results show that: The simulation accuracy of TVGM is improved in both Nash-Sutcliffe efficiency coefficient and water balance coefficient through data assimilation. The evapotranspiration accuracy for the sub-basin is improved. The data assimilation significantly modifies the hydrological process simulation under the influence of extreme climate and human water use. Therefore, the method is of potential practical value and an alternative tool for hydrological process simulation.